2015
DOI: 10.5901/jesr.2015.v5n1p313
|View full text |Cite
|
Sign up to set email alerts
|

Educational Theories of Cognitive Development

Abstract: Cognitive theories explain how behavior changes as a result of people 's perception, transformation, processing,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…Tolman (1930) berpendapat ketika individu mempelajari peristiwa tertentu maka akan menghasilkan kepuasan atas tujuan tertentu (Grider, 1993). Menurut Jean Piaget pengetahuan diciptakan melalui hubungan yang dinamis dan berkembang antara faktor internal, kognitif, dan lingkungan (Khalid, 2015). Faktor kognitif menurut Albert Bandura dapat berupa persepsi, keyakinan, ekspektasi dan sikap (Cook & Artino, 2016;Riley et al, 2016).…”
Section: Pendahuluanunclassified
“…Tolman (1930) berpendapat ketika individu mempelajari peristiwa tertentu maka akan menghasilkan kepuasan atas tujuan tertentu (Grider, 1993). Menurut Jean Piaget pengetahuan diciptakan melalui hubungan yang dinamis dan berkembang antara faktor internal, kognitif, dan lingkungan (Khalid, 2015). Faktor kognitif menurut Albert Bandura dapat berupa persepsi, keyakinan, ekspektasi dan sikap (Cook & Artino, 2016;Riley et al, 2016).…”
Section: Pendahuluanunclassified
“…2. The cognitivist, Kohler [13], a gestalt psychologist, suggested that learning occurs in the form of insight. The cognitive perspective of organizational learning suggested the organizations can learn and organizational learning to be a type of individual learning 3.…”
Section: 1mentioning
confidence: 99%
“…Numerous studies conducted on humans have demonstrated that early and appropriate psychosocial stimulation can result in significant enhancements in the development of both physical and mental processes (Jeong et al, 2016;Scaglioni et al, 2018;Sharma, 2023). Likewise, crucial elements that influence the physical development and cognitive advancement of preschool children encompass their family, residential environment, economic circumstances, psychosocial stimulation, socio-cultural factors, actual deprivation, community surroundings, and peer associations (Almeida et al, 2021;Duggan & Dennis, 2014;Khalid, 2015;Thomas et al, 2017). Inadequate psychosocial stimulation can result in developmental delays, impacting a child's capacity to excel at school as well as their future employment prospects and earning potential (Baitun Engle et al, 2011).…”
Section: Introductionmentioning
confidence: 99%